Representações sociais acerca de uma comunidade de prática enquanto espaço de formação continuada - Boneto, Cristiane (2016)
This paper aimed to identify evidence of social representations concerning the Community of Practice (CoP) as Continuing Education Space unveiled in the core of PUC / SP, participant in the Observatory Program of Education (OBEDUC / CAPES) consisting of Academy members, Basic Education teachers and undergraduate students. In our theoretical perspectives we have used: the concept of the Social Representation Theory (SRT) of Moscovici (2003), Gomez’s ideas (2002) regarding affection and affective domain in teaching Mathematics; Passos’s researches et al (2006) about the continuing Education Groups; Bourdieu habitus concept (1987) and Wenger identity concept (2001). As a tool for the data collection we have used: audio transcriptions of the recorded meetings, the narratives and memorials written by the participants and the footages of the activities carried out inside and outside the group (public schools in São Paulo). In order to support our studies, remarks and reflections we have used the quali-quantitative research and the Discourse of the Collective Subject Methodology (LEFEVRE, 2011) along with the use of the Software DSCSoft. This research was organized and written in multipaper format (articles compilation). In this path we have realized that, for every observed period, the evidence of social representations regarding the Community as continuing education space has changed. The need for mutual participation in the group constitution was legitimized and validated by its members, as well as the construction of an environment that valued and respected the expression of affection; and this construction was marked by tensions and conflicts. Our analysis results also pointed to the importance of a cultural diverse environment, where there is the doing it together and the reframing of the habitus and yet, the creation of a potentially positive environment, in which the individual and collective learning become the main goal to be achieved. We have considered the Communities of Practice as an important continuing Education space in which allows, not only the education, but also the personal and collective transformation of the teachers who have participated